Multiple reentrant glass transitions of soft spheres at high densities: Monotonicity of the curves of constant relaxation time in jamming phase diagrams depending on temperature over pressure and pressure - Schmiedeberg, Michael (Physical Review E, 2013)
By using molecular-dynamics simulations, we determine the jamming phase diagrams at high densities for a bidisperse mixture of soft spheres that interact according to repulsive power-law pair potentials. We observe that the relaxation time varies nonmonotonically as a function of density at constant temperature. Therefore, the jamming phase diagrams contain multiple reentrant glass transitions if temperature and density are used as control parameters. However, if we consider a new formulation of the jamming phase diagrams where temperature over pressure and pressure are employed as control parameters, no nonmonotonic behavior is observed.